SALSA : SAving Lives Staying Active to Promote Physical Activity and Healthy Eating - Lee, Rebecca E. (Hindawi Publishing Corporation, 2011)
Physical inactivity, poor dietary habits, and obesity are vexing problems among minorities. SAving Lives, Staying Active (SALSA) was an 8-week randomized controlled crossover design, pilot study to promote regular physical activity (PA) and fruit and vegetable (FV) consumption as a means to preventing weight gain among women of color. Participants completed measures of demographics, PA, and dietary habits. Women (N = 50; M = 42 years) who participated were overweight (MBMI = 29.7 kg/m(2); Mbody fat = 38.5%) and reported low levels of leisure time PA (M = 10.7 MET-min/wk) and FV consumption (M = 4.2 servings/day). All were randomized to a four-week (1) semiweekly Latin dance group or (2) internet-based dietary education group. All participants reported a significant increase in weekly leisure time PA from baseline (M = 10.7 MET-min/wk) to follow up (M = 34.0 MET-min/wk, P < .001), and FV consumption increased over time by group (P = .02). Data suggest that Latin dance interventions to improve PA and web-based interventions to improve dietary habits show promise for improving health among women of color.